ANALISIS HUKUM TERHADAP PENGALIHAN OBJEK JAMINAN FIDUSIA DIBAWAH TANGAN - irwan, irwan (Fakultas Hukum Universitas Ichsan Gorontalo, 2024)
In providing assistance in the form of loan funds to the debtor, the creditor asks for debt collateral from the debtor. The collateral can be in the form of movable objects, both tangible and intangible, and immovable objects, especially buildings which cannot be encumbered with mortgage rights, which are often called fiduciary guarantees. Definition of Fiduciary Guarantee according to Law of the Republic of Indonesia Number 42 of 1999 concerning Fiduciary Guarantee is a security right for movable objects, both tangible and intangible and immovable objects, especially buildings which cannot be encumbered with mortgage rights as intended in Law Number 4 of the Year 1996 concerning Mortgage Rights which remain in the control of the fiduciary, as collateral for the repayment of certain debts, which gives the Fiduciary Recipient a preferred position over other creditors. In a fiduciary agreement, the object that is used as the object of the fiduciary guarantee remains in the control of the owner of the object (debtor) and is not controlled by the creditor, so in this case it is handing over ownership of the object without handing over the physical object. The creditor entrusts the debtor to continue to use the collateral according to its function. However, even though the collateral remains in the control of the debtor, the debtor must have good faith to maintain the collateral as well as possible. Debtors are not permitted to transfer or lease to other parties objects of fiduciary security which are not inventory items without the approval of the creditor, because objects whose control is in the hands of the debtor are very risky to change hands. Transferring the object of fiduciary collateral under your own hands will have legal risks in the future. The debtor will be legally disadvantaged if the other party breaks their promise, hoping that that party wants to help pay the debt from the debtor to the creditor but in fact the party breaks their promise. The transfer of an object that is the object of a fiduciary guarantee under the hand is an imperfect transfer because the proof of ownership of an object of fiduciary guarantee is temporarily held by the party receiving the fiduciary as collateral. Before the fiduciary recipient executes the object that is the object of the fiduciary guarantee, it must be ensured that the object has been registered at the fiduciary registration office. If there is a transfer of rights to a fiduciary collateral object under the hands of the fiduciary giver or debtor, the fiduciary recipient can take legal action by executing the object that is the object of the fiduciary guarantee even though the object is controlled by another party.